Studies in power and class in Africa - Markovitz, Irving Leonard, 1934- (New York : Oxford University Press, 1987)
Sheds light on the importance of state, religion, ideology, gender, ethnicity, language, and international relations in determining policy and understanding society in general.
(cont.) The encadrement of the population : the bureaucratic development and restructuring of labor and business in South Africa. Transnational corporations and the national bourgeoisie : regional expansion and party realignment in South Africa / Ronald T. Libby -- Managing class structures in South Africa : Bantustans and the underbelly of privilege / Stanley B. Greenberg, Hermann Giliomee.
Includes bibliographical references (pages 375-386) and index.
Keywords: Power (Social sciences); Elite -- Africa; Social classes -- Africa; Women -- Political activity -- Africa; political system; political behaviour; ruling class; traditional culture; social change; political ideology; multinational enterprise; bureaucracy; statistical table; Africa -- Politics - Sociological perspectives; map; reference